PENGARUH SEMANGAT KERJA, DISIPLIN KERJA DAN PENGAWASAN TERHADAP KINERJA KARYAWAN PADA PT. PERKEBUNAN NUSANTARA V PKS SEI-INTAN ROKAN HULU - Hartati, Tuti; Sasmita, Jumiati; Rama, Rovanita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to determine effect spirit of work, discipline, and monitoring of work to performance of employees at PT. Perkebunan Nusantara V PKS Sei-Intan. The population in this study were all employees of the production of PT. Perkebunan Nusantara V PKS Sei-Intan totaling 146 people. While the sampling technique using census method. Analysis of data using multiple linear regression with SPSS program. Based on the results of data analysis known that the spirit of work, discipline of work, and monitoring significant effect on the performance of employees PT. Perkebunan Nusantara V PKS Sei-Intan, spirit of work significant effect on employee performance, disciplined work significantly influence employee performance, monitoring significant effect on employee performance. So it is expected to employees in order to increase knowledge and skills of the existing work in the company. Companies must pay attention to and improve employee spirit of work again so that the employee's performance can be improved further. Moreover, it also can make employees more satisfied in performing his job is to give appropriate salary for the work of the employees, the Company must provide a comfortable workplace for employees, the protection tools complete working cycle workplace air nice, thus employees will be more enthusiasm for work. If the employee morale in the company decreased, then the employee's performance will decline as well. Expected to companies that give strict sanctions against employees who are not disciplined in the work so that it can make employees always adhere to the rules and regulations made by a company. And it is expected that the leadership of the company to constantly improving rules or standards on work given so as to provide feedback tehadap the work of subordinates.Keywords: Spirit, Discipline, Monitoring, and Performance.